Age‐related risk factors for bacterial aetiology in community‐acquired pneumonia. Issue 8 (14th July 2016) - Sahuquillo‐Arce, José M.; Menéndez, Rosario; Méndez, Raúl; Amara‐Elori, Isabel; Zalacain, Rafael; Capelastegui, Alberto; Aspa, Javier; Borderías, Luis; Martín‐Villasclaras, Juan J.; Bello, Salvador; Alfageme, Inmaculada; de Castro, Felipe Rodriguez; et al.
ABSTRACT: Background and objective: The objective of this study was to evaluate the effect of age and comorbidities, smoking and alcohol use on microorganisms in patients with community‐acquired pneumonia (CAP). Methods: A prospective multicentre study was performed with 4304 patients. We compared microbiological results, bacterial aetiology, smoking, alcohol abuse and comorbidities in three age groups: young adults (<45 years), adults (45–64 years) and seniors (>65 years). Results: Bacterial aetiology was identified in 1522 (35.4%) patients. In seniors, liver disease was independently associated with Gram‐negative bacteria ( Haemophilus influenzae and Enterobacteriaceae ), COPD with Pseudomonas aeruginosa (OR = 2.69 (1.46–4.97)) and Staphylococcus aureus (OR = 2.8 (1.24–6.3)) and neurological diseases with S. aureus . In adults, diabetes mellitus (DM) was a risk factor for Streptococcus pneumoniae and S. aureus, and COPD for H. influenzae (OR = 3.39 (1.06–10.83)). In young adults, DM was associated with S. aureus . Smoking was a risk factor for Legionella pneumophila regardless of age. Alcohol intake was associated with mixed aetiology and Coxiella burnetii in seniors, and with S. pneumoniae in young adults. Conclusion: It should be considered that the bacterial aetiology may differ according to the patient's age, comorbidities, smoking and alcohol abuse. More extensive microbiological testing is warranted in those with risk factors for infrequent microorganisms. Abstract : We report patterns of rare causative organisms for community‐acquired pneumonia related to comorbidities such as liver disease, COPD, neurological illness diabetes, smoking and alcohol abuse in three age groups: young adults (<45 years), adults (45–64 years) and seniors (>65 years).